Real-Life Vehicle Routing with Non-Standard Constraints - Lee, Wee Leong (Institutional Knowledge at Singapore Management University, 2013)
Real-life vehicle routing problems comprise of a number of complexities that are not considered by the classical models found in vehicle routing literature. I present, in this paper, a two-stage sweep-based heuristic to find good solutions to a real-life Vehicle Routing Problem (VRP). The problem I shall consider, will deal with some non-standard constraints beyond those normally associated with the classical VRP. Other than considering the capacity constraints for vehicles and the time windows for deliveries, I shall introduce four additional non-standard constraints: merging of customer orders, controlling the maximum number of drop points, matching orders to vehicle types, and controlling mixed-load permutations between goods. My algorithm has been successfully implemented in a Third-Party Logistics (3PL) managed distribution operations of dairy products with reasonably good results and response time.